The complete sequence of the mitochondrial genome of Luchuan pig (Sus scrofa). (3rd May 2016) - Ran, Mao-Liang; He, Jun; Tan, Jing-ye; Yang, An-Qi; Li, Zhi; Chen, Bin
Abstract: Luchuan pig is one of the famous native breeds in China. In this study, we report the complete mitochondrial genome sequence of Luchuan pig for the first time, which is determined through the PCR-based method. The total length of the mitogenome is 16, 710 bp with the base composition of 34.67% A, 13.33% G, 25.82% T and 26.18% C, and an A + T (60.48%)-rich feature is detected, which contains 1 control region (D-loop region), 2 ribosomal RNA genes, 13 PCGs and 22 tRNA genes. The complete mitochondrial genome of Luchuan pig provides an important data in genetic mechanism and the evolution genomes.